2013
DOI: 10.9782/2159-4341-16.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of Dyslexia and Dyscalculia

Abstract: This study examined the prevalence of dyslexia and dyscalculia among persons with academic deficits in English Language and Mathematics in public primary schools in Ibadan metropolis. A correlational survey study, sampling 477 pupils who were between the ages of eight and 12 years, and in 4th and 5th grades with the use of four research instruments- the Myklebust Pupil Rating Scale (MPRS), the Slosson Intelligence Test- Revised Third Edition (SIT-R3), the Test of Pupil Reading Abilities Test (TPRA) and the Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For example, a comorbid diagnosis of dyslexia and dyscalculia (i.e., problems processing numerical information, learning arithmetic facts, and performing accurate or fluent calculations) occurs in approximately 40% to 65% of identified cases (Barbaresi, Katusic, Colligan, Weaver, & Jacobsen, 2005;Osisanya et al, 2013;Wilson et al, 2015), despite the fact that they are proposed to have different cognitive profiles (Landerl, Fussenegger, Moll, & Willburger, 2009). We would assert that children are more likely to be tested for dyslexia than dyscalculia, although no research was found to indicate the prevalence of one over the other.…”
Section: Educational Implicationsmentioning
confidence: 99%
“…For example, a comorbid diagnosis of dyslexia and dyscalculia (i.e., problems processing numerical information, learning arithmetic facts, and performing accurate or fluent calculations) occurs in approximately 40% to 65% of identified cases (Barbaresi, Katusic, Colligan, Weaver, & Jacobsen, 2005;Osisanya et al, 2013;Wilson et al, 2015), despite the fact that they are proposed to have different cognitive profiles (Landerl, Fussenegger, Moll, & Willburger, 2009). We would assert that children are more likely to be tested for dyslexia than dyscalculia, although no research was found to indicate the prevalence of one over the other.…”
Section: Educational Implicationsmentioning
confidence: 99%
“…Approximately 4 to 10% of the population is estimated to have dyslexia (Aleci, Piana, Piccoli, & Bertolini, 2010;Osisanya, Lazarus, & Adewunmi, 2013;Snowling & Melby-Lervåg, 2016). Dyslexia is defined as "a pattern of learning difficulties characterized by problems with accurate or fluent word recognition, poor decoding, and poor spelling abilities" (American Psychiatric Association, 2013, p. 67).…”
mentioning
confidence: 99%